Personal Eschatology in the Old English Dialogues of Gregory the Great: Text and Translation - Johnson, David F. (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
This article considers two monuments from early medieval England—the line drawings in Stowe 944 (the New Minster Liber vitae) and chapter 37 from the Old English translation of Gregory the great’s Dialogues, through the lens of James T. Palmer’s recent work on apocalypticism in the Middle Ages. Palmer (2014) argues that texts (and drawings like the ones in Stowe 944) can and should be considered apocalyptic, even though they present as depictions of individual, personal post-mortem events. They moreover serve a definite didactic purpose, and as such provide a clue as to the motivation behind the translation of Gregory’s Latin text into Old English.